Nitrogen and Phosphorus Removal Using a Novel Integrated System of Natural Zeolite and Lime - Montalvo-Martinez, S (2011)
Nitrogen and phosphorus can cause eutrophication problems in receiving waters. These nutrients can be eliminated by different wastewater treatments but they tend to be costly or require complex operations. With these reasons in mind, this work set out to study the behavior of a novel combined or integrated system with zeolite and lime for the removal of these chemical species. With the integrated treatment, excellent removals-98 % NH+ 4 , 100 % total phosphorus (TP), 79 % chemical oxygen demand (COD), 71 % BOD 5, 99 % of total suspended solids (TSS) and 100 % of fecal coliforms-were obtained. A sludge production of 4.4 % and 4.8 % of the wastewater total volume treated with lime was achieved. The final liquid effluent of the integrated system of natural zeolite and lime had a composition which was suitable for its discharge into sewerage systems and marine or continental waters (according to Chilean regulations), as far as the concentrations of nitrogen, phosphorus and total coliforms were concerned. Validated curves with their corresponding equations were obtained in this study for the removal of ammonia nitrogen and total phosphorus. These equations can theoretically be applied to estimate the removal of both parameters in studies or practical applications undertaken with operating conditions similar to those used in this work. Copyright © Taylor & Francis Group, LLC.